ANALISIS TOKOH DAN PENOKOHAN DALAM FILM ANIMASI TREASURE TREKKERS - Khoriah, Ismatul; Salim, Herli (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Different abilities of children demanded teachers to be rich in ideas when carrying out learning so that all children can understand learning well. Children’s high interest in watching animated films can be utilized as learning materials. Animated films are expected to make learning more effective for children. In this study, researchers analyzed characters and characterizations in the animated film Treasure Trekkers consisting of the main character, additional characters also characterization of the protagonist and antagonist so can be used as learning material following the material for class 4 sub-theme 1 about telling characters in fiction stories because children face difficulty to tell characters in fiction stories. Treasure Trekkers is one of the animated films that are suitable as learning material. This film tells the story of three explorers who explore the world, on a mission to find the most valuable treasures, namely kindness, and friendship. In this film, children will learn about the characters with various characters they have, so it will be easy for children to tell the characters in fiction stories. The researcher uses a qualitative approach because produces data in the form of a description containing a detailed explanation of the topics discussed in a tested manner, a content analysis method that is to discuss in full the contents of something to be analyzed. Researchers found characters and characterizations in the animated film Treasure Trekkers and describe the message that each character carries aiming to make students easier to achieve basic competencies in telling characters in fiction stories. Students also will learn in an effective and not boring.